The relative age effect is associated with career sport engagement in alpine ski racers attending training centers. (September 2021) - DeCouto, Brady S.; Cowan, Rhiannon L.; Thomas, Joseph L.; Fawver, Bradley; Steidl-Müller, Lisa; Williams, A. Mark
Abstract: Objectives: The relative age effect (RAE), a phenomenon where relatively older athletes in a selection year are overrepresented, has been evidenced across different sports and age-levels. No published reports have assessed if the RAE influences practice time for relatively younger athletes, which could contribute to sport success. In this study, we compared patterns for performance and sport engagement between earlier-born and later-born adolescent alpine ski racers from Austria (AUT) and the United States (US). Design and methods: We assessed birth quarter distribution and performance trends using a performance (FIS) database (US: N  = 2172; AUT: N  = 516), and sport engagement through administering a practice history questionnaire to athletes attending ski academies/boarding schools (US: N  = 169; AUT: N  = 209). Results: Chi-square analyses revealed an underrepresentation of athletes born later in both samples. Mixed regressions only showed performance improvements for later-born US ski racers. Relatively younger athletes in Austria engaged in more individual and group practice over time, while no clear practice patterns emerged for US ski racers. Conclusions: Results suggest that later-born ski racers in Austria need to practice more to bridge skill/performance gaps with their relatively older peers. Additionally, later-born ski racers who do not put in extra practice may be deselected. Practice time may be less pivotal for relatively younger ski racers in the US due to less strict talent filtration systems. Coaches can ameliorate the RAE by dedicating more attention during practice towards developing relatively younger athletes who are transiently overshadowed by older, higher-performing athletes. Highlights: The relative age effect was evident in both alpine ski racing samples. Performance improvements in later-born ski racers were only evident in the US. Later-born Austrian ski racers engaged in more practice throughout development. Coaches should dedicate more attention to athletes with age-related disadvantages.